2021
DOI: 10.1093/humrep/deab159
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling in fetuses conceived by ARTs: fresh versus frozen embryo transfer

Abstract: STUDY QUESTION Do fetuses from frozen embryo transfer (FET) present signs of cardiac remodeling and suboptimal function similar to those observed in fetuses from fresh embryo transfer (ET)? SUMMARY ANSWER Fetuses from both fresh ET and FET present signs of fetal cardiac remodeling and suboptimal function, with more pronounced changes after fresh ET as compared to FET. WHAT IS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
1
10
2
Order By: Relevance
“…2). Consistent with previous studies showing cardiac morphological changes in ART fetuses [6,19], in the present study, we demonstrated a globular enlarged LV and a larger RV in ART fetuses. From a pathophysiological perspective, a spherical dilated shape will weaken the contractile properties of the ventricle [20,21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2). Consistent with previous studies showing cardiac morphological changes in ART fetuses [6,19], in the present study, we demonstrated a globular enlarged LV and a larger RV in ART fetuses. From a pathophysiological perspective, a spherical dilated shape will weaken the contractile properties of the ventricle [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…With regard to diastolic performance, we observed increased mitral E' in ART fetuses. However, previous studies described unchanged or reduced mitral E' [6,19]. Thus, the changes in mitral E' that are reported here need to be further validated.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The observed differences between our three study groups could have been triggered by their different intrauterine vasoactive and hormonal milieu 56 , 57 , 58 , 59 , 60 , 61 , but also by changes in cardiac function: brain and heart development take place simultaneously in utero and often share morphogenetic programs 62 . Fetuses conceived by ART show differences in growth and cardiac shape and function compared with SC fetuses, fresh ET being associated with fetal smallness 6 , 63 and cardiac remodeling and dysfunction 64 , 65 , and frozen ET with macrosomia 63 , hypertensive disorders of pregnancy 5 , 66 and milder cardiac changes 65 , 67 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Boutet et al compared fetal echocardiography parameters at 28-33 weeks of gestation in pregnancies conceived by fresh and frozen embryo transfer to spontaneously conceived pregnancies. 48 Surprisingly, the results demonstrated that cardiac remodeling is more prominent in cases of in vitro fertilization with fresh embryo transfer.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 93%